2012
DOI: 10.3329/jesnr.v5i1.11595
|View full text |Cite
|
Sign up to set email alerts
|

Urea Super Granule: A Good Source of Nitrogen on Growth Yield and Profitability of Cabbage in Sylhet

Abstract: An experiment was conducted in Sylhet under AEZ-20 (Eastern Surma-Kushiyara Floodplain) during 2007-08 and 2008-09 to find out the effect of Urea Super Granule (USG) on cabbage. There were five treatments viz. T1: recommended nitrogen (N) dose as prilled urea (PU), T2: recommended N dose as USG, T3: 10% less than recommended dose of N as USG, T4: 20% less than recommended dose of N as USG, and T5: farmers practice (average of 20 farmers N dose used as PU) used in the experiment. Results revealed that yield of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
2
2
0
Order By: Relevance
“…As a consequence, the rice plant had a constant supply of nitrogen during its growth cycle, which eventually led to a more grain yield. The aforementioned findings are in line with those of presented in [32], who found that deep insertion of USG was superior than PU and N loss was likewise negligible.…”
Section: Discussionsupporting
confidence: 91%
“…As a consequence, the rice plant had a constant supply of nitrogen during its growth cycle, which eventually led to a more grain yield. The aforementioned findings are in line with those of presented in [32], who found that deep insertion of USG was superior than PU and N loss was likewise negligible.…”
Section: Discussionsupporting
confidence: 91%
“…This resulted in continuous supply of available nitrogen throughout the growth period of rice plant, which ultimately gave the higher grain yield. The above results are well correlated with the findings of Sarker et al (2012) reported that deep placement of USG was more effective over PU and N loss was also minimal. They also reported that USG can save 10-20% N fertilizer instead of traditional PU fertilizer.…”
Section: Effect Of Pu and Usg And Their N Dose On Mineral Nitrogen In...supporting
confidence: 90%
“…The economic analysis also showed that the use of urea super granule was economically viable to cultivate the tomato. Sarker et al (2012) showed that USG was more effective over PU, and N loss was also minimum than that of PU where 10-20% N fertilizer could be saved by using USG instead of traditional PU. They also reported that all the rate of N as USG showed better performance than that of normal PU for cabbage yield and found economically viable.…”
Section: Economic Analyses and Evaluationmentioning
confidence: 98%